(untitled) (Journal of Philosophy Culture and Political Science, 2025)
The article is dedicated to studying the role of cultural symbols in shaping urban identity in the context of modern society, characterized by globalization and urbanization. In recent decades, cultural symbols have acquired particular significance as they play a key role in preserving cultural heritage and transmitting traditions, which is especially important amid the rapid changes in urban environments. The primary goal of this research is to analyze the relationship between cultural symbols and the collective perception of urban spaces, as well as to assess their influence on social values and identity. The study covers both tangible and intangible symbols, including architectural structures, monuments, rituals, customs, and other elements that hold deep cultural significance for the local community. An important aspect of the work is an interdisciplinary approach that combines methods from cultural studies, urbanism, and sociology, allowing for a comprehensive examination of the topic. The methodological basis of the research includes both qualitative and quantitative methods, such as content analysis, visual analysis, interviews, and surveys. This ensures a thorough analysis and deep understanding of how cultural symbols are perceived and interpreted by different groups of urban residents. The research results showed that cultural symbols play a fundamental role in shaping urban identity, influencing residents’ perceptions and attitudes toward their environment. Data analysis confirmed that cultural symbols are an important element of urban space, contributing to the strengthening of collective memory and social cohesion. The importance of these symbols in the context of urban planning and cultural policy cannot be underestimated, as their integration into urban development promotes the preservation and popularization of cultural heritage. The significance of the study lies in its contribution to the development of theoretical and practical aspects of cultural studies and urbanism. The findings can be used in developing strategies aimed at improving the urban environment, as well as in strengthening cultural identity and social cohesion in modern urban life. The work opens new perspectives for further research and practical application of the results in urban planning and cultural policy. Keywords: design, ethnic style, national pattern, fashion, tradition